Bilateral trade between Paraguay and the United States of America: an analysis of its development during the period 1994-2016 - Ruiz Díaz Arce, Guido Arturo (2018)
The purpose of this paper is to analyze the development of trade between Paraguay and the United States of America in the period 1994-2016. The methodology used for this has been bibliographic-documentary and different tools were used, among which are: the Revealed Comparative Advantage Index, the Trade Intensity Index, the Grubel-Lloyd Index and the Gravity Model. Some of the most relevant results are that Paraguay has comparative advantages in terms of production of certain agricultural products and the United States presents these advantages in machine and mineral products. In addition, it be verified that the distance, the difference of languages and Paraguay`s geographical situation could affect the bilateral trade.